Non-coding RNAs at the Eukaryotic rDNA Locus: RNA–DNA Hybrids and Beyond. Issue 15 (10th July 2020) - Vydzhak, Olga; Luke, Brian; Schindler, Natalie
Abstract: The human ribosomal DNA (rDNA) locus encodes a variety of long non-coding RNAs (lncRNAs). Among them, the canonical ribosomal RNAs that are the catalytic components of the ribosomes, as well as regulatory lncRNAs including promoter-associated RNAs (pRNA), stress-induced promoter and pre-rRNA antisense RNAs (PAPAS), and different intergenic spacer derived lncRNA species (IGSRNA). In addition, externally encoded lncRNAs are imported into the nucleolus, which orchestrate the complex regulation of the nucleolar state in normal and stress conditions via a plethora of molecular mechanisms. This review focuses on the triplex and R-loop formation aspects of lncRNAs at the rDNA locus in yeast and human cells. We discuss the protein players that regulate R-loops at rDNA and how their misregulation contributes to DNA damage and disease. Furthermore, we speculate how DNA lesions such as rNMPs or 8-oxo-dG might affect RNA–DNA hybrid formation. The transcription of lncRNA from rDNA has been observed in yeast, plants, flies, worms, mouse and human cells. This evolutionary conservation highlights the importance of lncRNAs in rDNA function and maintenance. Graphical abstract: Unlabelled Image Highlights: LncRNAs arise from transcription by three different RNA polymerases and affect rDNA replication and transcription by formation of RNA–DNA hybrids in cis and in trans . PAPAS, pRNA and IGSRNAs are rDNA derived lncRNAs that form RNA–DNA hybrids (R-loops and triplexes). A myriad of proteins regulate the rDNA locus, including regulators of RNA–DNA hybrids, like RNase H enzymes, topoisomerases, helicases and others. The repetitive rDNA locus is a hotspot for the accumulation of genomic ribonucleotides (rNMPs) or base modifications like oxidative stress induced 8-oxo-dG modifications.